Implementasi Algoritma Knuth-Morris-Pratt Pada Perancangan Aplikasi Kamus Istilah Komputer Berbasis Web - Aprilia Monika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A dictionary is a reference book that contains a collection of vocabularies with explanations and their meanings arranged in alphabetical order. The computer dictionary is a very practical application where to find a term in the computer world, it is no longer difficult to carry a very thick dictionary book or carry several kinds of books to find an understanding of the computer term itself, and of course it is easier to search and shorten the time in use. . In this study, the researcher applied the Knuth-Morris-Pratt algorithm in the computer term search feature. The Knuth-Morris-Pratt algorithm has the advantage of finding matches in large files and the results of this study are a web-based computer term dictionary application, with this dictionary application the search for a computer term becomes faster and more efficient.